Rosenberg Self-Esteem Scale: Ukrainian Adaptation and Psychometric Properties - Veldbrekht , Olena; Zinchenko , Nadiia; Tavrovetska , Nataliia (Insight: the psychological dimensions of society, 2025)
Rosenberg Self-Esteem Scale is one of the most popular and well-proven tools for measuring an individual’s attitude towards themselves. Such popularity is due to the accessibility and effective-ness of the methodology, as well as the long his-tory of its use. Although the scale is well known to domestic psychologists, there is no scientific justification for its use in Ukraine. The purpose is to present the results of the adaptation and testing of the methodology based on a Ukrainian sample. Methods. In accordance with modern standards of cultural adaptation of psychometric instruments, the scale was forward and backward translated and pretested in a sample of 25 psy-chology students. The testing of the methodology included three waves of research, involving 537 participants aged 11–45 years, among them 168 men and 369 women. The results confirmed the high psychometric quality of the instrument. Themean self-esteem score in the sample was 28.26 points with a standard deviation of 5.49. Global self-esteem does not differ between sexes but is significantly age-dependant: the lowest level was found in adolescent groups. The scale has high internal consistency and reliability (Cronbach’s alpha value is .88, Guttman’s lambda – .89). All items have sufficient discriminatory power (Fer-guson delta values from .61 to .75). The retest reli-ability coefficient (re-measurement at an interval of 12–15 weeks) was 0.74. Principal component analysis confirmed the unidimensional struc-ture of the scale, but confirmatory factor analysis proved that the two-factor model showed a better fit to the empirical data. Self-esteem indicators on the Rosenberg scale obtained in adolescent and student samples closely correlate with similar parameters measured using other instruments: emotional valence of self-descriptions in the pro-jective method “Who Am I?”, global and specific self-assessments in various life spheres according to the “Self-Perception Profile” by S. Harter, gen-eral self-efficacy, life satisfaction, the proximity of the real and ideal “Self”, self-confidence. The sensitivity of the results to the severity of the in-dividual’s social desirability motivation is shown. The level of self-esteem directly correlates with indicators of psychological well-being, negative-ly – with the severity of stress. Discussion and Conclusions. The adapted Ukrainian version of the Rosenberg Self-Esteem Scale is a convenient, reliable, and valid tool for measuring a person’s global self-esteem, which can be used in adoles-cent groups starting from 11–12 years of age. The possibility of distinguishing two dimensions of the scale, defined by positively and negatively worded items (self-respect and self-contempt), requires additional clarification.
Keywords: self-awareness; global self-es-teem; positive and negative self-esteem; self-con-cept; self-image; self-perception; self-attitude; psychological well-being